INTERPRETASI WANITA CADAR PADA TAYANGAN PROPAGANDA KELOMPOK ISIS - Praditiani, Sasha (Jurnal Visi Komunikasi, 2017)
Many terrorist cases that occur in the world or Indonesia in the name of Islam that make Muslims especially veiled women increasingly cornered because people assume that veiled women are radical Muslims and associate them with terrorist groups or ISIS. This research identifies how the process of interpreting veiled women in Tangerang against ISIS through propaganda videos spread in cyberspace. Stuart Hall's theory of reception analysis verbal and non-verbal communication, understanding veils in Islam, understanding of ISIS groups, understanding signs and meanings and psychosocial development. Critical paradigm with descriptive research type, with in-depth interviews with adolescents and adults. Basically the interpretations of the interviewees who have tapered on the same thing, namely the ISIS group is not a reflection of Islam, and does not support it, it can be seen from the results of analysis that three of the four interviewees included in the oppossitional category by stating that groups ISIS is a group that carries a cruel and inhuman image. One person entered into the Negotiation Position category in the teen category.